2021
DOI: 10.3390/app112411972
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Graphenic Carbon Produced by Pulsed Laser Ablation of Sacrificial Carbon Tapes

Abstract: This paper reports on the pulsed laser deposition of nanocarbon films on metal and dielectric substrates, using high-purity sacrificial carbon tape as a carbon source on a neutral gas background. The films were characterized by X-ray diffraction (XRD), photoelectron (XPS) and Raman spectroscopy. The XRD and Raman structural analyses revealed that the synthesized films have a graphenic nanocrystalline turbostratic structure, with sp2 clusters about 15–18 nm in size, depending on the laser fluence. A significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The possible existence of a laser energy threshold is also suggested by the work of Ershov et al [151,152], which showed that increasing the energy density of a 20 ns Nd:YAG laser caused an increase in defects and the formation of smaller sp 2 crystallites in graphenic films deposited on metallic and metal-oxide substrates. These works, unlike most other examples of PLD of graphene and graphene-like materials, were not carried out in vacuum or a reduced pressure atmosphere, but in He at atmospheric pressure, and by using a sacrificial nanocarbon tape as the target rather than graphite.…”
Section: Effect Of Laser Parameters and Deposition Conditionsmentioning
confidence: 83%
See 1 more Smart Citation
“…The possible existence of a laser energy threshold is also suggested by the work of Ershov et al [151,152], which showed that increasing the energy density of a 20 ns Nd:YAG laser caused an increase in defects and the formation of smaller sp 2 crystallites in graphenic films deposited on metallic and metal-oxide substrates. These works, unlike most other examples of PLD of graphene and graphene-like materials, were not carried out in vacuum or a reduced pressure atmosphere, but in He at atmospheric pressure, and by using a sacrificial nanocarbon tape as the target rather than graphite.…”
Section: Effect Of Laser Parameters and Deposition Conditionsmentioning
confidence: 83%
“…The first attempts at the growth of graphene films were made with the fundamental and second harmonic of nanosecond Nd:YAG lasers (respectively, 1064 nm and 532 nm) [121,122,149,150], and several recent works have also employed them [134,135,151,152].…”
Section: Effect Of Laser Parameters and Deposition Conditionsmentioning
confidence: 99%
“…The main peaks of C1s at 284.4 and 285.2 eV are attributed to the sp 2 and sp 3 carbon of CC bonding, in addition to pi–pi* and C–O bonds. 79,80…”
Section: Resultsmentioning
confidence: 99%
“…The main peaks of C1s at 284.4 and 285.2 eV are attributed to the sp 2 and sp 3 carbon of CC bonding, in addition to pi-pi* and C-O bonds. 79,80 Fig. 10 shows the possible molecular interactions between the polymer blend and CNTs.…”
Section: Msde Papermentioning
confidence: 99%